2018
DOI: 10.5505/kpd.2018.65487
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation Of Compassion Level Of Nursing Students In A Health College (Turkish)

Abstract: Object: The aim of this study is to determine the level of compassion and the factors that affect the level of compassion of nursing students in a health college. Methods: The descriptive study has been conducted in a nursing department of a health college. "Introductory Information Form" by the researchers in accordance with the literature and developed by Pommier (2010) "Compassion Scale" has been used as the data collection tool. Analyzes of the data were conducted by using frequency, Mann-Whitney U Test, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 7 publications
(11 reference statements)
3
18
0
4
Order By: Relevance
“…The nurses in this study had a high compassion level. In the literature, some studies have reported similar results to the present study (Arlı et al 2018;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Büyük et al 2021;Karadağ et al 2018). In the study by Arkan (2020), nurses had a medium compassion level (Arkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The nurses in this study had a high compassion level. In the literature, some studies have reported similar results to the present study (Arlı et al 2018;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Büyük et al 2021;Karadağ et al 2018). In the study by Arkan (2020), nurses had a medium compassion level (Arkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, compassion enables nurses to establish therapeutic communication with patients and facilitates their ability to understand patients, recognize their emotions and needs and meet their spiritual needs (Uslu et al 2016). Studies indicated that nurses have high compassion levels (Arlı et al 2018;Büyük et al 2021;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Karadağ et al 2018). Compassionate care practices, which may be a quality indicator, increase patient satisfaction levels and comfort of care and make patients feel better (Çınar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A nine-question personal information form prepared by the researchers using the literature [1][2][3]26…”
Section: The Personal Information Formmentioning
confidence: 99%
“…Öğrencilerin %63,1'inin bölümü isteyerek seçtiği, %68,8'inin bölümden memnun olduğu, %60,4'ünün hemşirelik hizmeti almadığı belirlenmiştir (Tablo 1). Öğrencilerin %84,9'u hastanede diğer insanlardan duygu bulaşı yaşadığını, %60,3'ü hastanın çektiği acıdan orta çalışmalar mevcuttur (18,22). Empatik eğilimin cinsiyet değişkeninden etkilenmemesine karşın kadın öğrencilerde empatik eğilim düzeyinin daha yüksek olduğu belirlenmiştir.…”
Section: Bulgularunclassified
“…Öğrencilerin sosyodemografik değişkenlere göre merhamet ölçeği puanlarına bakıldığında; merhamet ölçeği toplam puanı ile cinsiyet değişkeni arasındaki fark istatistiksel olarak anlamlı bulunmamıştır (p>0,05) (Tablo 4). Literatürde merhametin cinsiyet değişkeninden etkilendiğini bildiren çalışmalar mevcuttur (18,22). Empatik eğilimin cinsiyet değişkeninden etkilenmemesine karşın kadın öğrencilerde empatik eğilim düzeyinin daha yüksek olduğu belirlenmiştir.…”
Section: Bulgularunclassified